Expectations of new technologies in nursing care among hospital patients in Germany – an interview study - Klawunn, Ronny; Albrecht, Urs-Vito; Dierks, Marie-Luise (Frontiers in Psychology, 2023)
Introduction: New technologies will be increasingly available for nursing care, including robots, patient mobilisation devices, digital event detection or prevention equipment. Technologies are expected to support nurses, increase patients' safety and reduce costs. Yet, although these technologies will significantly shape patients' experience, we need to learn more about patients' perspectives regarding new technology in care. This study aims to investigate attitudes, expectations, worries and anticipated implementation effects of new assistive technology in nursing care by patients.Methods: Qualitative, guided, semi-open interviews were conducted. The recruitment was carried out on in a trauma surgery ward of a university hospital in Germany. Eight different technologies were presented via video clips and additional information to the patients, followed by in-depth discussions. The interviews were analysed using qualitative evaluative content analysis. The Consolidated cCriteria for Reporting Qualitative rResearch (COREQ) Checklist was used to ensure study quality.Results: Study participants anticipate different outcomes for the implementation of new nursing technology: 1) For patients, they consider a the potential for improvement in health and well-being as well as for their hospital stay experience, but also fear possible health risks or social or emotional factors like loss of autonomy or loneliness. 2) For professional nurses, participants expect relief from physically stressful work routines; however, they might be replaced by machines and lose their employment 3) For the nursing process, safety and quality improvements for care delivery may encounter a negative quantification of human life and risks of constant surveillance.Patients identify opportunities, challenges and shortcomings of nursing technology implementation. They describe nuanced and mixed accounts of patients' perspectives that are structured in a 'continuum of anticipated effects' of implementing technology in our article. The results can inform future implementation strategies.